Discharge performance of side gates with different shapes - Kartal, Veysi; Emiroglu, M. Emin; Yuksel, M. Fatih (Iwa Publishing, 2025)
Flow measurement and water level control in open channels are vital to water management. Lateral intake structures are commonly used for different purposes in civil and environmental engineering applications. Flow characteristics of rectangular, triangular, and semi-circular shapes were experimentally investigated using 357 runs under subcritical flow conditions. Correlation analysis was conducted to determine the effect of various parameters on the discharge coefficient. Upstream Froude number (F-1), the ratio of the gate opening to the upstream flow depth, and the gate length to flow depth ratio are influential for all side gates. However, the ratio of the gate opening to the gate length is also influential for triangular side gates. Discharge coefficient of the semi-circular side gate is relatively higher than that of the other tested gates within the range of 0.05<0.40; the discharge coefficient of the triangular side gate is relatively higher than that of the other shaped gates for 0.40<0.98 and the efficiency of the triangular side gate decreases more than that of the other gates as the downstream Froude number value increases. A reliable equation for side gates was developed. Good agreements were obtained between the proposed equations and the experimental data.
Keywords: correlation test; discharge coefficient; gate; lateral flow; open channel